(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Korea, educational facilities are managed after issues are detected. Furthermore, due to imprecisely estimated maintenance costs, there are problems in managing educational facilities such as excessive budgets, etc. it is impossible to accurately estimate costs for various cases such as repairs and damages. Thus, the overall maintenance costs were analyzed based on probability of cases that may occur. This study proposes a system that predicts maintenance subjects and maintenance costs using probability values and that predicts the total maintenance cost through simulations. This study used simulations to accurately predict maintenance costs in various unexpected situations. The study was carried out by classifying into three categories according to each feature. The features were described according to the type of each item and simulation of the categorized items were produced separately to calculate the expected price. In the case of ‘annual fixed expenses’, the total of the maintenance cost tended to increase with a secondary curve where the slope gradually grows with time. In the case of ‘irregular expenses due to repairs/changes caused by minor failures’, maintenance cost had a certain cycle according to a failure rate according to the life of each item and an inflation rate of 1.9% was applied to show a tendency for occurrence to grow. In the case of ‘Replacement/repair costs according to the scheduled period for the entire educational facility’, the simulation results showed that each item had a constant cycle depending on the replacement period and that facility maintenance costs did occur. This study presumed data for simulations, but did not verify it. By supplementing such limitations, it will be possible to produce a reliable simulation model. The expected effect of reducing budget waste by predicting the exact cost of educational facilities through simulation.